Synthesis of Integrated Layered‐Spinel Composite Cathode Materials for High‐Voltage Lithium‐Ion Batteries up to 5.0 V. Issue 11 (17th July 2015) - Zhao, Jianqing; Ellis, Sarah; Xie, Zhiqiang; Wang, Ying
Abstract: Integrated layered‐spinel composite materials are synthesized through the facile decomposition of Li4 Mn5 O12 ‐based spinel materials at 900 °C. The intergrowth of spinel Li1+ z Mn2− z O4 (0< z <0.33) and Li‐rich layered Li2 MnO3 components is examined by using X‐ray diffraction and high‐resolution transmission electron microscopy. Such a layered‐spinel composite material and its derivatives obtained by doping transition‐metal ions are evaluated as high‐voltage cathode materials for advanced lithium‐ion batteries up to 5.0 V versus Li/Li + . The Ni‐doped composite cathode shows remarkably high‐energy and high‐power characteristics with high‐voltage plateaus at approximately 4.7 V, delivering desirable discharge capacities of 130, 115, and 90 mAh g −1 at current densities of 25, 125, and 500 mA g −1, respectively, along with excellent cycling stability. This work provides a facile route for preparing the integrated layered‐spinel composite materials as promising high‐voltage cathode materials for lithium‐ion batteries. Abstract : LIB up to expectations : Integrated layered‐spinel composite materials are prepared through the decomposition of Li4 Mn5 O12 ‐based spinel materials at high annealing temperature. After doping with additional transition metal ions, such layered‐spinel compounds can serve as high‐voltage cathode materials for advanced lithium‐ion batteries up to 5.0 V versus Li/Li + . The Ni‐doped composite cathode shows remarkably high‐energy and high‐power characteristics, along with excellent cycling stability.